Typologies of Trade Strategies and Their Links with Export Promotion Strategy - Jatuliavičienė, Gražina (Ekonomika, 1999)
Trade strategies accepted in a country can explain why countries facing the same external environment, achieve different results of export performance. The article draws attention to both theoretical evolution of development policies and trade strategies and their impact on an economy. Of course, the success of exporting depends on the conditions of external markets, i. e. on demand conditions (slow economic growth and unstable demand reduce possibilities for exporting), but supply conditions, which are affected by the trade strategy in a country, determine the place of exports in an economy and the significance of export promotion strategy and activities. This is especially meaningful for evaluating the case of the Lithuanian economy which was affected by the change of development policies from inward-oriented to outward-oriented, liberalising its highly protectionist trade regime and which is only beginning its export promotion activities.